New Wave 4u : the photocopy shop / Muhammad Helmi Rahim, Mohd Badrul Hisham Dalwis and Abbe Zyeid Jafar - Rahim, Muhammad Helmi; Dalwis, Mohd Badrul Hisham; Jafar, Abbe Zyeid (Faculty of Information Management, 2002)
Business fieid is an economic activity that is very profitable, but full commitments, patience and hard working are essentials in executing a project. Prophet Muhammad states that in al hadith; "90% of the wealth is from the business".